PEMANFAATAN EKSTRAK KULIT KAYU GERUNGGANG (Cratoxylon arborescens BI) UNTUK PENGAWETAN KAYU KARET (Hevea brasiliensis) DARI SERANGAN RAYAP TANAH (Coptotermes curvignathus Holmgren) - Daviyana, Syarifah Ashria; Wardenaar, Evy; Yanti, Hikma (Universitas Tanjungpura, 2013)
The objective of this research was to determine the anti-termite properties of bark extract of gerunggang (Cratoxylon arborescens Bl) on rubber wood (Hevea brasiliensis) and determine the optimum concentration levels in rubber wood (H. brasiliensis) to inhibit the attack of subterranean termites (Coptotermes curvignathus Holmgren). Variables in this study are the observation of retention gerunggang bark extract (C. arborescens), the mortality of subterranean termites (C. curvignathus) and weight loss of rubber wood sample (H. brasiliensis). The results showed that the highest retention of rubber wood found at concentration 5% with a value of 2.2480 kg/m3, the highes termite mortality at concentration 4% and 5% with a value 100% and the lowest wood sample weight loss found at concentrations of 5% to value of 13.2791%. Key words : bark extract, Cratoxylon arborescens, rubber wood, Coptotermes curvignathus Holmgren